Rancangan Bangun Turbin Mikrohidro Tipe Archimedes Screw Dengan Kapasitas Daya 560 Watt - Zainuri Anwar; Beta Saud Parsaroan; Edi Sunarso (Universitas Batanghari Jambi, 2021)
The performance of a micro-hydro turbine was influenced by several factors, namely the design and the enviromental. This study aims to obtain the appropriate design parameters for the manufacture of screw turbines. This research was focused on blade dimensions and turbine screw pitch distance. The calculations were performed using several screw turbine fixing formulations. The design results show that the optimum blade diameter and turbine pitch range are 0.213 m and 0.312 m at 0.2 m3 / s of turbine inlet water flow and 563.3 Watt turbine shaft output power. The turbine screw test results of the design were carried out in the river flow of Puri Kedaton Housing, Pematang Gajah Village, Rt 13, Jambi Province. The test results show that the highest turbine power occurs at 30 kg shaft loading with a turbine output power of 445 Watts and an efficiency of 78.9%.